Molecular detection of Thecaphora frezzi in peanut (Arachis Hypogaea L.) seeds - Cazon, Luis Ignacio; Conforto, Erica Cinthia; Fernandez, Franco Daniel; Paredes, Juan Andrés; Rago, Alejandro Mario (2017)
Thecaphora frezii is the causal agent of peanut smut, important disease in the Argentine production area. The pathogen can be dispersed by kernels, through surface contamination or small lesions. The aim of this work was to design specific primers to develop a Polymerase Chain Reaction assay for the detection of Thecaphora frezii in peanuts kernels. The ITS region of four T. frezii isolates was amplified and sequenced. A consensus sequence was obtained and a pair of primers specific for the pathogen, named TF-2F and TF- 2R, was synthesized. The primers were used for specificity and sensitivity tests. The former test involved a PCR using DNA from T. frezii and other seed-transmitted pathogens (S. rolfsi, S. minor, Fusarium solani and S. sclerotiorum). A 190 bp fragment was obtained for the T. frezii isolates, whereas no amplification was observed for the remaining pathogens. For the sensitivity test, positive results were observed at concentrations up to 3x10-4 pg of the target DNA. The specificity of this method, along with its sensitivity, makes it an important tool for epidemiological studies of peanut smut.